Holocaust museums, Holocaust memorial culture, and individuals: a Constructivist perspective - Oztig, Lacin Idil (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2023)
There is a rich body of literature examining the contribution of Holocaust museums to the Holocaust memorial culture by focusing on their educative, awareness-raising, and memorializing functions. In this context, ample attention has been devoted to these museums' exhibitions, educatory activities, reenactment practices, digital strategies, as well as their historical and architectural narratives. This article brings a novel perspective to the literature by giving an account of how Holocaust museums act as a medium through which individuals contribute to the Holocaust memorial culture from a Constructivist perspective. It argues that Holocaust museums do not treat individuals as passive recipients of the Holocaust memorial culture, but actors who could exercise agential capacities in relation to the Holocaust memorial culture. This argument is illustrated by case studies of the United States Holocaust Memorial Museum (USHMM), the Berlin Jewish Museum, and the Anne Frank House. It is shown that these museums offer platforms through which individuals actively contribute to the Holocaust memorial culture by encouraging them to conduct and share their Holocaust-related research, donating Holocaust-related objects, and engaging in social activities to diffuse related norms and messages.
Keywords: Holocaust museums; Holocaust memorial culture; individuals; agency; Constructivism; SOCIAL CONSTRUCTION; POLITICS; Arts & Humanities - Other Topics